Per una naturalizzazione del concetto di aspettativa in economia a partire dal(la) fine: J. M. Keynes e S. Freud - Ceschi, Maria Vittoria (Metapsychologica - rivista di psicanalisi freudiana, 2024)
For a naturalization of the concept of expectation in economics starting from the end: J. M. Keynes and S. Freud. The article explores the concept of expectation in economics through a naturalization approach, primarily drawing on the ideas of John Maynard Keynes and Sigmund Freud. It contrasts the theoretical framework of the rational expectations hypothesis (and its developments) with Keynesian concepts of conventions and animal spirits, emphasizing the role of uncertainty and the ends or motives in economic behavior. The article first examines the biological foundation through anticipatory systems theory and then the drive foundation through metapsychology. It demonstrates how the evolution of expectations is determined by their differing relationships with the drive end, understood as a combination of object and aim (satisfaction). This naturalized understanding of expectations enables their formulation within a theory of living systems: complex and creative.